2014
DOI: 10.3389/fpsyg.2014.01336
|View full text |Cite
|
Sign up to set email alerts
|

The good, the bad, and the timely: how temporal order and moral judgment influence causal selection

Abstract: Causal selection is the cognitive process through which one or more elements in a complex causal structure are singled out as actual causes of a certain effect. In this paper, we report on an experiment in which we investigated the role of moral and temporal factors in causal selection. Our results are as follows. First, when presented with a temporal chain in which two human agents perform the same action one after the other, subjects tend to judge the later agent to be the actual cause. Second, the impact of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 22 publications
(37 reference statements)
3
27
0
Order By: Relevance
“…These results confirm previous studies that show that the violation of a norm is a stronger trigger for attributing blame than the moral status of the outcome (Reuter et al, 2014). A 2 x 2 ANOVA with Action and Outcome as independent factors, and participant's rating as dependent measure was carried out.…”
Section: Unbeknownst Tosupporting
confidence: 76%
“…These results confirm previous studies that show that the violation of a norm is a stronger trigger for attributing blame than the moral status of the outcome (Reuter et al, 2014). A 2 x 2 ANOVA with Action and Outcome as independent factors, and participant's rating as dependent measure was carried out.…”
Section: Unbeknownst Tosupporting
confidence: 76%
“…A second related study made a valuable contribution to the current work already, in providing a framework for the vignettes in Experiment 2 (Reuter et al, 2014). In the original study, they examined the role of norm violations and temporal order in causal selection.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, rather than using a rating scale, Reuter et al (2014) had their participants make a forced choice between the two agents in the scenario. They found that the agent who violated a norm was more likely to be selected as the cause, and indeed this is compatible with the causal superseding effect, but it does not distinguish whether the varied actor was seen as more causal or whether the fixed actor was seen as less causal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While we will focus on these two accounts here, it should be noted that these are not the only two plausible explanations in the literature nor are they the only two worth discussing. Just a few notable examples are the work ofAlicke 1992, Cushman 2013, Malle et al 2014, and Reuter et al 2014 …”
mentioning
confidence: 99%